Working toward Better Pay : Earning Dynamics in Ghana and Tanzania - Falco, Paolo; Kerr, Andrew; Paci, Pierella; Rijkers, Bob (Washington, DC: World Bank, 2014)
Improving access to productive employment is a key policy challenge, especially in low-income countries (LICs), where the only asset in abundance is labor. Building on ongoing research on earnings mobility, this study uses unusually rich longitudinal data from Ghana and Tanzania to identify engines of, and barriers to, earnings and earnings mobility. It examines the role of individual characteristics such as gender, age, and skills and characteristics of the job, but it also focuses on the role of job switches for example, moves into and out of self-employment. It zooms in particularly on the drivers of transitions between low-paying and high-paying jobs, and addresses questions such as whether being low paid is a transitory or permanent phenomenon, and whether it has a scarring effect on an individual's employment prospects. The extent to which earnings dynamics differ for women and young adults is also discussed in detail. The cross-country comparison of earnings dynamics and labor market transitions helps shed light on the institutional factors that promote labor market mobility and entrepreneurship. The report is organized as follows: chapter one gives introduction. Chapter two presents a brief review of related literature. Chapter three gives a descriptive overview of the labor markets in the two countries. Chapter four examines the determinants of earnings levels. Chapter five examines determinants of earnings growth. Chapter six focuses on low-pay and high-pay transitions and analyzes whether the experience of being in a low-paying job undermines an individual's future earnings prospects. Chapter seven discusses key policy implications.